Synthesis of high fracture toughness of hydroxyapatite bioceramics - Tan, Chou Yong; Singh, Ramesh; Ranna, Tolouei; Iis, Sopyan; Teng, Wan Dung (Trans Tech Publications, Switzerland, 2011)
The sinterability of magnesium oxide (MgO) doped hydroxyapatite (HA) ranging from 1 to 10 wt% when sintered at 1150°C was investigated in terms of phase stability, bulk density, Young's modulus, Vickers hardness and fracture toughness. The addition of up to 1 wt% MgO as sintering additive was found to be beneficial in promoting the densification of HA. Further addition of MgO in the HA matrix would deteriorate its densification properties. Similar results were observed for its stiffness and Vickers hardness. Nevertheless, the fracture toughness of HA was greatly enhanced by the incorporation of 5 wt% MgO. An increased toughness of up to 35% was obtained for the MgOdoped HA when compared to the undoped HA. This improvement is associated to the smaller grain size of the doped sample as compared to the undoped HA.